2015
DOI: 10.1038/ejcn.2014.277
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids in relation to incident mobility disability and decline in gait speed; the Age, Gene/Environment Susceptibility-Reykjavik Study

Abstract: BACKGROUND/OBJECTIVES Low intake of long chain polyunsaturated fatty acids (PUFAs) are associated with physical disability; however, prospective studies of circulating PUFAs are scarce. We examined associations between plasma phospholipid n – 3 and n – 6 PUFAs with risk of incident mobility disability and gait speed decline. SUBJECTS/METHODS Data are from a subgroup of the Age, Gene/Environment Susceptibility–Reykjavik Study, a population-based study of risk factors for disease and disability in old age. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
(42 reference statements)
1
16
1
Order By: Relevance
“…In contrast, another study showed no associations between self-reported omega-3 PUFAs and physical performance measures such as chair rise, grip strength, and gait speed, casting doubt over the role of omega-3 PUFAs in physical function (Rousseau et al 2009). In AGES-Reykjavik study, a population-based study of risk factors for disease and disability in old age, higher concentrations of omega-3 PUFAs and, particularly, DHA may protect women from impaired mobility but does not appear to have such an effect in men (Reinders et al 2015b). Several limitations of this study need to be mentioned.…”
Section: Discussionmentioning
confidence: 86%
“…In contrast, another study showed no associations between self-reported omega-3 PUFAs and physical performance measures such as chair rise, grip strength, and gait speed, casting doubt over the role of omega-3 PUFAs in physical function (Rousseau et al 2009). In AGES-Reykjavik study, a population-based study of risk factors for disease and disability in old age, higher concentrations of omega-3 PUFAs and, particularly, DHA may protect women from impaired mobility but does not appear to have such an effect in men (Reinders et al 2015b). Several limitations of this study need to be mentioned.…”
Section: Discussionmentioning
confidence: 86%
“…Further, this study provides novel preliminary evidence that greater dietary and serum omega-6/omega-3, signifying excess omega-6 LC-PUFAs intake and blood values relative to omega-3s, may adversely influence physical and metabolic health in chronic stroke survivors. While we are the first to examine these relationships in a cohort of chronic stroke survivors, this study supports data from non-stroke populations suggesting that higher dietary and systemic concentrations of omega-3 LC-PUFAs, compared to omega-6s, protect against accelerated age-and disease-associated decline of physical and psychosocial functioning and development of insulin resistance and chronic inflammation [12][13][14].…”
Section: Discussionsupporting
confidence: 75%
“…The concentrations of fatty acids were expressed as a relative percent of the sum of the 24 fatty acids reported in NHANES as shown in Table S1 . The concentration of LCn-3 PUFAs was determined in the same manner as previous publications [ 9 , 15 , 16 ], as the sum of EPA, DHA and docosapentaenoic acid (DPA) divided by total fatty acids (See Table S1 for all fatty acids included in the “total fatty acids” denominator).…”
Section: Methodsmentioning
confidence: 99%